Ineffectiveness of Adjunctive Topiramate in Infants with Refractory Partial Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
A double-blind, placebo-controlled, international study of topiramate in 149 infants aged 1-24 months (mean age 12 months) with refractory partial-onset seizures is reported from Seattle Children's Hospital, WA.